2001
DOI: 10.1038/sj.ijo.0801748
|View full text |Cite|
|
Sign up to set email alerts
|

High prevalence of diabetes, obesity and dyslipidaemia in urban slum population in northern India

Abstract: BACKGROUND AND AIMS:In this study, a prevalence survey of various atherosclerosis risk factors was carried out on hitherto poorly studied rural -urban migrants settled in urban slums in a large metropolitan city in northern India, with the aim of studying anthropometric and metabolic characteristics of this population in socio-economic transition. DESIGN: A cross-sectional epidemiological descriptive study. SUBJECTS: A total of 532 subjects (170 males and 362 females) were included in the study (response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
222
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(250 citation statements)
references
References 25 publications
22
222
6
Order By: Relevance
“…These epidemiological, population-based studies were conducted between 1998 and 2003 in two metropolitan cities in north India by two investigators. Two studies were conducted in New Delhi by our group (AM, NKV): the first on urban adult population 12 and the second on subjects aged 14-25 years. 13 The first study from New Delhi included subjects residing in an urban resettlement colony.…”
Section: Study Design and Sampling Methodsmentioning
confidence: 99%
“…These epidemiological, population-based studies were conducted between 1998 and 2003 in two metropolitan cities in north India by two investigators. Two studies were conducted in New Delhi by our group (AM, NKV): the first on urban adult population 12 and the second on subjects aged 14-25 years. 13 The first study from New Delhi included subjects residing in an urban resettlement colony.…”
Section: Study Design and Sampling Methodsmentioning
confidence: 99%
“…Because ED and CVD share many of the same risk factors, the relationship between CVD and ED is a very valid concern. Among Asian Indians, there is rising trend of CAD with disease often being more extensive and severe than their Western counterpart [11,12]. Despite this, there are limited data on the prevalence of ED and its association with angiographically documented CAD in these patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there are limited data on the prevalence of ED and its association with angiographically documented CAD in these patient populations. Patients were divided into groups based on IIEF-5 scores as no ED (22)(23)(24)(25), mild (17)(18)(19)(20)(21), mild to moderate (12)(13)(14)(15)(16), moderate (8)(9)(10)(11), and severe (<7) ED [13]. Patients with abnormal parameters were assessed by cardiologists by echocardiography, stress test and if necessary coronary angiography (Non-Invasive or Invasive).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these measurements, detailed information was collected on their dietary habits and sedentary lifestyle behaviour along with other sociodemographic characteristics. Information on the woman's perception about her own weight and weight-management behaviour was also collected, which is the main response variable in the present paper.Sample selection, response rate and sample size Earlier studies on obesity in India and other developing countries have shown that overweight and obesity are predominant in urban areas and among women (16,(18)(19)(20)(21)(22)(23)(24)(25) . Therefore, only urban primary sampling units were chosen for the follow-up survey in Delhi.…”
mentioning
confidence: 99%